On the effectiveness of supplier development programs: the role of supply-side moderators - Saghiri, Soroosh; Wilding, Richard D. (Elsevier, 2021)
Given the managerial/financial commitments needed for supplier development programs, buying firms need to be selective of the suppliers they engage for development. This paper examines the moderating role of five supply-side factors (i.e. supplier size, supply share, product complexity, buyer-supplier integration, and the supplier's management systems) in the relationship between supplier development and supplier performance, through a structural model, which is developed theoretically, and tested empirically using survey data of 142 firms. The results indicate that when supplier development is in the form of buyer direct involvement, its impact on supplier performance is significantly moderated by supplier size, product complexity, buyer-supplier integration, and the supplier's management systems. Meanwhile, the impact of supplier development, in the form of assessment/certification, is moderated by buyer-supplier integration. The outcomes of this paper fill the gaps in the existing knowledge of supplier development, and show the sensitivity of supplier development programs to some newly introduced supply-side factors.
Keywords: Supplier development; Supplier performance; Supplier size; Product complexity; Supply share; Supplier integration; Management system